Here's link to the answer:
cutt.us/tWGpn
Answer: The answer is 1600.
Step-by-step explanation:
U can’t that’s ur answer bc u can’t add if there’s an x
Answer:
4
Step-by-step explanation:
m=(y2-y1)/(x2-x1)
m=(6-(-2))/(3-1)
m=(6+2)/(2)
m=8/2
m=4
Answer:
see the explanation
Step-by-step explanation:
we know that
A gross is equal to 120 ones or ten dozen
what is 15 tens - 1 gross
we know that
15 tens means ----> That you are adding 10, 15 times or multiplying 10 by 15, which gives you
![10(15)=150](https://tex.z-dn.net/?f=10%2815%29%3D150)
1 gross means ---> That you are adding 10, 12 times or multiplying 10 by 12
which gives you
![10(12)=120](https://tex.z-dn.net/?f=10%2812%29%3D120)
so
The algebraic expression of 15 tens - 1 gross is equal to
![150-120=30](https://tex.z-dn.net/?f=150-120%3D30)
Convert to word expression
3 tens